Structural Health Monitoring – a Review with the Emphasis on Low-Frequency Methods - KOŁAKOWSKI, P. (Engineering Transactions, 2014)
Structural Health Monitoring (SHM) is a fast-developing, interdisciplinary field of research having its roots in vibroacoustics and non-destructive testing and evaluation. Fast development of the area is due to the fact that SHM is heavily stimulated by the engineering problems of maintenance and safe operation of technical infrastructure. The use of SHM is slowly becoming a standard in high-cost, modern infrastructure. Therefore, the possibility of application should always be on the horizon of any related research work. Thus far, the majority of SHM applications have been demonstrated in civil, aerospace and mechanical engineering. This paper reviews the main achievements and points out the current trends in this field with the emphasis on low-frequency methods.